1982
DOI: 10.1159/000241601
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Changes in Mitochondrial Respiration of the Rabbit Heart

Abstract: Oxidative metabolism and citrate synthase activity during the perinatal period were assessed in isolated rabbit heart mitochondria at 27 days’ gestation (27 dpc), 1 day postpartum (1 dpp) and 10 dpp. Oxygen consumption was measured during state 3 and state 4 respiration using the following substrates: glutamate, α-ketoglutarate, pyruvate/malate, succinate/rotenone, acetate, palmitylcarnitine, and palmityl CoA/carnitine. Results obtained from fetal and neonatal animals were compared to values obtained from adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As newborn rats have a low ability to synthesize carnitine during the first postnatal week (Hahn, 1981) ln vitro studies using tissue homogenates (Warshaw, 1972 ;Glatz and Veerkamp, 1982 ;Wolfe, Maxwell and Nelson, 1978), isolated mitochondria (Warshaw and Terry, 1970 ;Werner et al, 1982) or isolated perfused organ (Werner et al, 1983b) have shown that the heart of fetal rats, rabbits, pigs and calves has a very low capacity for long-chain fatty acid oxidation, even in the presence of carnitine. Similarly, compared to adults, the rate of palmitate oxidation is reduced in skeletal muscle homogenates (Glatz and Veerkamp, 1982 ;Carroll et al, 1983 ;Wolfe, Maxwell and Nelson, 1978 ;Mac Larty et al, 1984) and in kidney slices (Wolfe, Maxwell and Nelson, 1978 ;Freund, Sedraoui and Geloso, 1984), lung (Warshaw, Terry and Ranis, 1980) and small intestine (Warshaw, 1974) of fetal rats and pigs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As newborn rats have a low ability to synthesize carnitine during the first postnatal week (Hahn, 1981) ln vitro studies using tissue homogenates (Warshaw, 1972 ;Glatz and Veerkamp, 1982 ;Wolfe, Maxwell and Nelson, 1978), isolated mitochondria (Warshaw and Terry, 1970 ;Werner et al, 1982) or isolated perfused organ (Werner et al, 1983b) have shown that the heart of fetal rats, rabbits, pigs and calves has a very low capacity for long-chain fatty acid oxidation, even in the presence of carnitine. Similarly, compared to adults, the rate of palmitate oxidation is reduced in skeletal muscle homogenates (Glatz and Veerkamp, 1982 ;Carroll et al, 1983 ;Wolfe, Maxwell and Nelson, 1978 ;Mac Larty et al, 1984) and in kidney slices (Wolfe, Maxwell and Nelson, 1978 ;Freund, Sedraoui and Geloso, 1984), lung (Warshaw, Terry and Ranis, 1980) and small intestine (Warshaw, 1974) of fetal rats and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of heart (Wittels and Bressler, 1965 ;Warshaw and Terry, 1970 ;Warshaw, 1972 ;Mersmann and Phinney, 1973 ;Aprille, 1976 ;Wolfe, Maxwell and Nelson, 1978 ;Werner et al, 1982Werner et al, , 1983a, skeletal muscle (Wolfe, Maxwell and Nelson, 1978 ;Glatz and Veerkamp, 1982 ;Carroll et al, 1983) and kidney (Wolfe, Maxwell and Nelson, 1978 ;Freund, Sedraoui and Geloso, 1984) to oxidize NEFA increases shortly after birth in rats, rabbits, pigs and calves. In contrast, it has been reported that substantial fatty acid oxidation occurs only 2 weeks after birth in dog heart (Breuer et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glucose is the only metabolic substrate provided in our model. Because adult myocardium relies more on fatty acid oxidation than does neonate myocardium (15,16), our model may place the adult heart at a relative disadvantage. Werner et al (1 6 ) did note that 10-d-old rabbit hearts have an increased ability to oxidize palmitylCoA compared with the fetal heart.…”
Section: Resultsmentioning
confidence: 99%
“…1 ) In mammals, during the suckling period, 50-70 % of the caloric intake is in the form of lipids (Ferré et al, 1986). In rats (Page, Krebs and Williamson, 1971 ;Foster and Bailey, 1976 ;Robles-Valdes, McGarry and Foster, 1976) as well as in humans (Bougneres et al, 1982(Bougneres et al, , 1986 (Wittels and Bressler ;Warshaw, 1972;Mersmann and Phinney, 1973 ;Aprille, 1976 ;Wolfe, Maxwell and Nelson, 1978 ;Werner et al, 1982Werner et al, , 1983 and skeletal muscle (Wolfe, Maxwell and Nelson, 1978 ;Glatz and Veerkamp, 1982 ;Caroll et al, 1983) (Newsholme, 1976 al., 1978, 1983) and thus increases lactate production from glucose. A similar mechanism has been postulated in the human newborn oxidizing ketone bodies (Bougnères et a/., 1983).…”
Section: Introductionmentioning
confidence: 99%